BROWN ROOT ROT DISEASE OF CASHEW IN WEST NUSA TENGGARA: DISTRIBUTION AND ITS CAUSAL ORGANISM - Supriadi Supriadi; E.M. Adhia; D. Wahyuno; S. Rahayuningsih; N. Karyani; M. Dahsyat (Indonesian Journal of Agricultural Science, 2004)
Brown root rot disease is a major constraint on cashew plantation in Pekat District, West Nusa Tenggara. Its causal agent has not been characterized. This paper describes efforts to study the pathogen, distribution and loss. Field study was conducted in Pekat District in 2003. Laboratory  experiments to isolate and test the causal agent were conducted in the Indonesian Spices and Medicinal Crops Research Institute, Bogor.  Research results showed that the disease was found widespread in several villages in Pekat District, such as Pekat, Beringin Jaya, Sorinomo, and Nangamiro. Total number of died cashew trees was 1,075 equals to 5,106 kg kernel yield lost, worth Rp20.5 million. Infected trees showed leaf yellowing and defoliation leading to die. The lateral and taproots near collar were encrusted with gravel, earth, and brown mycelia sleeves. The fungus produced arthrospores and brown pigmentation on agar medium containing 0.05% gallic acid. An isolate of the fungus induced typical disease symptoms following inoculation on 5 month-old cashew seedlings. These results indicated that the causal agent of mass decline of cashew in Pekat District is Phellinus noxius. In field, the fungus also infects a barrier tree (Lannea coromandelica [Houtt.] Merr.) (Anacardiaceae), locally known as kedondong pagar or kayu bantenan.